(untitled) (Scientific journal of the Fergana State University, 2026)
This article studies helminths found in small poultry farms and family enterprises in the foothills, foothills and steppe regions of the Fergana Valley, as well as in turkeys kept free on the ground in household conditions. It also studies the level and intensity of helminth infestation in turkeys and the relationship of parasite-host interaction with environmental factors and seasons. As a result of the studies, 59.1% of turkeys were infected. 25 species of helminths were recorded in them. Helminthological studies revealed a high prevalence and intensity of helminths in spring and summer.